Evaluation of Tinospora cordifolia stem extract bioactive content and anticancer activity against breast cancer cells - Annisa Yuslinda; Rosyadah Nuraini; Kamila Fairuz Sarah; Ulfa Siti Mariyah; Lestari Sri Rahayu; Widodo Nashi (BIO Web of Conferences)
Breast cancer remains a major public health challenge, highlighting the importance of finding new therapeutic approaches, including the use of traditional plants with unstudied medicinal properties. This study aims to explore the bioactive potential of Tinospora cordifolia stem extract by investigating the content of flavonoids, phenols, terpenoids and alkaloids as well as the cytotoxic and apoptotic effects on T47D breast cancer cells. Analysis of bioactive compound content revealed a total flavonoid content of 29.7 ± 0.30 mg QE/g extract, a total phenol content of 120.4 ± 4.25 mg GAE/g extract, a total terpenoid content of 2.41 ± 2.18 mg LE/g extract and a total alkaloid content of 2.55 ± 0.27 mg LE/g extract. Cytotoxicity tests on T47D cells using the WST-1 assay showed a dosedependent decrease in cell viability with an IC50 of 571.3 ± 33.41 µg/ml. Furthermore, at a concentration of 2IC50, T. cordifolia stem extract can induce apoptosis by 36.7 ± 4.19%. These results suggest that T. cordifolia has considerable anticancer activity, although further studies are needed to understand its mechanism of action and evaluate its potential in breast cancer therapy.